2015
DOI: 10.1186/s40623-015-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change of EIA asymmetry revealed by a beacon receiver network in Southeast Asia

Abstract: To reveal the temporal change of the equatorial ionization anomaly (EIA) asymmetry, a multipoint satellite-ground beacon experiment was conducted along the meridional plane of the Thailand-Indonesia sector. The observation includes one station near the magnetic equator and four stations at off-equator latitudes. This is the first EIA asymmetry study with high spatial resolution using GNU Radio Beacon Receiver (GRBR) observations in Southeast Asia. GRBR-total electron contents (TECs) from 97 polar-orbit satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The data gap caused by the solar panels can be seen on the north side of the mapping image. An enhancement of the total count of the red channel caused by an enhancement of the 630-nm emission can be seen around the latitude of 5° S. This enhancement was interpreted to be caused by the EIA, because the magnetic latitude of the enhancement is consistent with the typical magnetic latitude of the EIA (e.g., Watthanasangmechai et al 2014Watthanasangmechai et al , 2015. The total counts of the enhancement on the east side of the FOV were larger than those on the west side.…”
Section: Horizontal Airglow Structuresmentioning
confidence: 80%
“…The data gap caused by the solar panels can be seen on the north side of the mapping image. An enhancement of the total count of the red channel caused by an enhancement of the 630-nm emission can be seen around the latitude of 5° S. This enhancement was interpreted to be caused by the EIA, because the magnetic latitude of the enhancement is consistent with the typical magnetic latitude of the EIA (e.g., Watthanasangmechai et al 2014Watthanasangmechai et al , 2015. The total counts of the enhancement on the east side of the FOV were larger than those on the west side.…”
Section: Horizontal Airglow Structuresmentioning
confidence: 80%
“…The RMSE is larger in low latitude regions than in middle and high latitude regions and shows two peaks near 20 ±  . The reason for this may be the EIA, which makes the variation of the F2-layer in low latitude regions a non-linear dynamic process and a result of complex physical systems [47]. It can be seen that the RMSE is larger in equinoxes than in solstices over both the northern and southern hemispheres.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…The electrodynamical process in EIA regions is complicated, the asymmetry and strength of EIA would be mainly affected by the disturbed neutral wind and electric field. Watthanasangmechai et al [2015] indicated that the neutral wind is typically considered as the primary source of EIA interhemispheric asymmetry, whereas the zonal electric field is secondary. Thus, when the normal neutral wind is disrupted, the interhemispheric asymmetry may be changed.…”
Section: Discussionmentioning
confidence: 99%